Effects of Maternal and Post-Weaning High-Fat Diet on Leptin Resistance and Hypothalamic Appetite Genes in Sprague Dawley Rat Offspring - Choi, Joo Sun (Clin Nutr Res, 2018)
The defective satiation signaling may contribute to the etiology of obesity. We investigated how dietary modification during maternal (pregnancy and lactation) and post-weaning affects obesity, insulin resistance (IR) and hypothalamic appetite responses in offspring in adulthood. Pregnant female SD rats were randomly allocated to either maternal high-fat diet (43% energy from fat) or control diet (12% energy from fat) until the end of suckling. After weaning for additional 4 weeks, half of the offsprings were continuously fed the same diet as the dam (C-C and H-H groups); the remainder received the counterpart diet (C-H and H-C groups). The long-term high-fat diet during maternal and post-weaning period (H-H group) led to susceptibility to obesity and IR through the significant increases of hypothalamic orexigenic genes compared to the maternal and post-weaning control diet group (C-C group). In contrast, the hypothalamic expression levels of anorexigenic genes, apolipoprotein E, leptin receptor, and activated signal transducer and activator of transcription protein 3 were significantly lower in H-H group with elevations in circulating insulin and leptin and body fat mass. However, dietary changes after weaning (H-C and C-H groups) partially modified these conditions. These results suggest that maternal and post-weaning diet conditions can potentially disrupt hypothalamic neuronal signal irrelevantly, which is essential for leptin's regulation of energy homeostasis and induce the risk of offspring to future metabolic disorders.